The Venezuelan integration policy: the case of mercosur (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The policy of economic integration in the case of Venezuela, it is a central goal within the framework of the Constitution and national development plans and places particular emphasis on South American integration, serving the people and beyond the strictly economic. Hence, the Venezuelan government has applied for admission to MERCOSUR, which is manifested by the signing of the framework agreement in 2005 and the Protocol of Accession in 2006, but to date no has been the ratification of the Protocol by the Senate of Paraguay, so that Venezuela is not yet a full member of the integration agreement. Since the economics are essential in an integration agreement, the following question arises, do we really, from the economic point of view, Venezuela has no advantages over Mercosur? This article attempts to advance an answer to this question, concluding that Venezuela's integration policy, in the case of MERCOSUR, not due to economic reasons. We do an analysis of trade specialization index, the index of similarity and the rate of intra-industry trade to determine the economic conditions in Venezuela over the same and effectiveness of the Venezuelan political integration within the framework of its economic policy. In the field of space research is delimited to MERCOSUR (Argentina, Brazil, Uruguay and Paraguay) and Venezuela, while temporarily investigation covers the period 1999-2008.
Keywords: economic integration; trade indexes; Mercosur; Venezuela